Case report: Corneal endothelial degeneration and optic atrophy in dentatorubral-pallidoluysian atrophy quantified by specular micrography and optical coherence tomography - Takizawa, Shunya; Mitamura, Hiroto; Ohnuki, Yuko; Kawai, Kenji; Ohnuki, Yoichi; Nagata, Eiichiro; Takahashi, Wakoh (Frontiers in Neurology, 2022)
Introduction: Dentatorubral-pallidoluysian atrophy (DRPLA) is an autosomal dominant neurodegenerative disease with various neurological manifestations. Corneal endothelial degeneration and optic atrophy have been reported separately; however, there are no reports of corneal endothelial degeneration with optic atrophy. Cases: Herein, we present four related patients with DRPLA: two patients (69-year-old female and 80-year-old male) who exhibited both corneal endothelial degeneration and optic atrophy and another two (49- and 51-year-old females, respectively) who exhibited only corneal endothelial degeneration. We quantified the reduction in corneal endothelial cell density (ECD) and hexagonality using specular microscopy and thinning of the circumpapillary retinal nerve fiber layer (RNFL) using optical coherence tomography (OCT). Conclusions: This is the first report of DRPLA accompanied by corneal endothelial degeneration and/or optic atrophy, which were both quantified based on the corneal ECD and circumpapillary RNFL thickness using specular micrography and OCT, respectively. The pathophysiological mechanism is unclear; however, the involvement of the nuclear receptor TLX interacting with atrophin-1 may be implicated in ophthalmic manifestations of DRPLA. Therefore, we recommend performing specular micrography and/or OCT when patients with DRPLA experience visual disturbances.